Dengue hemorrhagic fever and bradycardia (Panacea Journal of Medical Sciences, 2022)
Background: The numbers of patients with dengue fever are increasing in the world and affecting the health of society. Overcrowding urbanization and increase in travelling are having a direct impact on the improvement in the numbers of patients. The causes of relative bradycardia like Hypothyriodism, Electrolyte imbalance and structural heart disease were also having a significant impact on the health of the human. The relative importance of immune and neural mechanisms and also any direct cardiac pathology in the aetiology of dengue associated with relative bradycardia.Materials and Methods: The researcher was conducted from July 2018 to December 2020. The researcher has selected the sample size of 100 patients from tertiary care hospital which was attached to the research institution. Most of the patients were having a history of fever and symptoms like vomiting, joint pain, diarrhoea, abdominal pain and headache.Results: The analysis of collected data of patients shows that 98 people were having a high fever, 43 were facing issues related to vomiting, 11 patients were having malaise and 12 patients were having body ache. These symptoms have shown that dengue is affecting health and leading to relative bradycardia. The lack of treatment and delay in the care services and support can be life-threatening for the patients.Discussion: The relative bradycardia is a notable feature among the patients of dengue and affecting the respiratory and heart rate of the patients. However, this condition is reported among the positive dengue IgM/NS patients. The proper investigation of the relative bradycardia situation among the patients is beneficial for the care professional to identify the method of treatment and providing clinical care.